Solve the theory and design of a linear system to achieve stability and study the inverted pendulum on a cart using (MATLAB) - Imad Omara Shebani Etomi; Zakariya Ali Saeid; Amnnah Ali Algmati; Almabrouk omir Darbi; Amed Abdulsalam Kakah (Surman Journal of Science and Technology, 2026)
This research paper addresses the basic principles of studying the solution of two problems: solving the problem of "linear system theory and design" and setting the reference (r) to be a series of alternating steps with a sufficient time interval to achieve a steady state, and the second problem is studying an inverted pendulum on a cart and choosing appropriate values ​​for the system parameters. MATLAB is used to simulate the system using the original nonlinear equations (Open-loop system).